Toward a holistic model of sustainable investment decision-making in SMEs: a structural approach in a developing economy - Dedrix Stephenson Bindeeba; Eddy Kurobuza Tukamushaba; Rennie Bakashaba (Future Business Journal)
Abstract Sustainable investment practices are increasingly recognized globally, yet their uptake among Small and Medium Enterprises (SMEs) in developing economies is insufficiently understood. This study investigates the factors influencing sustainable investment decision-making among 372 SMEs in Kampala and Wakiso, Uganda. Data were collected using convenience sampling through a mixed-mode questionnaire administered via face-to-face interviews and online forms. Integrating Institutional Theory, Resource-Based View, and the Theory of Planned Behavior, the research examines how environmental risk exposure, perceived regulatory clarity, government incentives, technological capability, financial access, competitive pressure, and business network strength shape the perceived value of sustainable investment. Employing covariance-based structural equation modeling, the study tests both direct and mediated effects. Results reveal that environmental risk negatively influences perceived value, while technological capability, financial access, network strength, and competitive pressure positively influence it. In contrast, perceptions of regulatory strength and government support do not exhibit significant effects, likely due to low enforcement and institutional trust. The perceived value of sustainable investment strongly predicts actual sustainability-oriented investments, confirming its mediating role. These findings offer practical insights for policymakers and development actors seeking to foster sustainable transitions in resource-constrained environments.